Mechanical soil and water conservation - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
In semi-arid areas, where water scarcity and poor soil condition pose significant threats to agricultural production and to the livelihood of individual smallholders and communities, water and soil management are critical for food/water security. Limited renewable freshwater and erratic rainfall patterns in those areas restrict the reliance on irrigation, making water conservation strategies more pressing and necessary [1]. Moreover, implementing advanced irrigation systems may be challenging due to limited resources and a lack of technical expertise [2]. For smallholder farmers, the adoption of irrigation systems, such as drip irrigation, is limited by further constraints such as high costs, limited access to finance, lack of technical support, and may not be suitable for all local conditions and cropping systems [3]. Under these constraints, promoting water and soil conservation strategies practices as part of a broader water management package to increase agricultural productivity at the farm level becomes crucial for ensuring sustainable agricultural production.